Female sex as a risk factor in minimally invasive direct coronary artery bypass grafting - Gofus, Jan; Vobornik, Martin; Sorm, Zdenek; Dergel, Martin; Karalko, Mikita; Harrer, Jan; Pojar, Marek (Scandinavian cardiovascular journal, 2019)
Objectives. Female sex has been generally accepted as a risk factor for short-term mortality and adverse events in surgical myocardial revascularization. However, there have been no data published yet about sex differences in minimally invasive settings. The aim of our study was to analyse short- and long- term outcomes of minimally invasive direct coronary artery bypass grafting (MIDCAB) in terms of sex comparison. Design. We retrospectively analysed the in-hospital data of all patients (n = 384) undergoing MIDCAB at our department in years 2006-2016. Subsequently, the data were enriched by long-term outcomes from national registries. Results. There were 96 women in our group (25%). Females were significantly older (67.1 vs 63.8 years; p < .01) and were more often diabetic (43.8% vs. 31.8%; p < .01). Surgery time was longer in females (160 vs 155 min; p = .02), and also the need for blood transfusion (19.8% vs 10.4%; p = .02) and wound complications (15.6% vs 2.4%; p < .001) were more frequent in women. After multivariate analysis, the wound complications risk (p < .001) and longer surgery times (p < .01) remained associated with sex. All-cause in-hospital mortality (2.1% vs 0.7%; p = .26), long-term mortality (p = .73), and the risk of coronary intervention post-operatively (p = .16) were the same in both sexes. Higher incidence of cardiac cause of death in women was observed from long-term aspect (69.6% vs 38.7%; p = .01). However, after adjustment it lost its significance. Conclusions. Female sex is not connected with higher risk of mortality or other major events in MIDCAB. Wound healing complications remain the leading attribute associated with female sex.
Keywords: Wound Healing; Hospital Mortality; retrospektivní studie; Humans; Risk Assessment; lidé středního věku; Middle Aged; mortalita v nemocnicích; Time Factors; nemoci koronárních tepen; Coronary Artery Disease; Risk Factors; mužské pohlaví; minimally invasive surgery; long-term effects; Coronary artery bypass grafting; Sex Factors; výsledek terapie; rizikové faktory; koronární bypass; časové faktory; Coronary Artery Bypass; Postoperative Complications; beating heart coronary artery bypass; Treatment Outcome; ženské pohlaví; pooperační komplikace; sexuální faktory; hodnocení rizik; sex differences; lidé; hojení ran; Aged; postoperative complications; senioři; Male; Retrospective Studies; Female